Hadith #2277 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ali ibn Abi Talib; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Nafi' b. 'Ujayr b. 'Abd Yazid b. Hashim; Ujayr bin 'Abd Yazid bin Hashim; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
While I was sitting with AbuHurayrah, a Persian woman came to him along with a son of hers. She had been divorced by her husband and they both claimed him. She said: AbuHurayrah, speaking to him in Persian, my husband wishes to take my son away. AbuHurayrah said: Cast lots for him, saying it to her in a foreign language. Then her husband came and asked: Who is disputing with me about my son? AbuHurayrah said: O Allah, I do not say this, except that I heard a woman who came to the Messenger of Al
Grade: Sahih

Hadith #2982 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Abi Layla عبد الرحمن بن أبي ليلى; Abu Ja'far al-Razi أبو جعفر الرازي; Ali ibn Abi Talib; Matruf bin Tarayf al-Harithi مطرف بن طريف; Yahya bin Abi Bkyr يحيى بن أبي بكير واسمه نسر (Sunan Abi Dawud)
Yazid ibn Hurmuz said that when Najdah al-Haruri performed hajj during the rule of Ibn az-Zubayr, he sent someone to Ibn Abbas to ask him about the portion of the relatives (in the fifth). He asked: For whom do you think? Ibn Abbas replied: For the relatives of the Messenger of Allah (ﷺ). The Messenger of Allah (ﷺ) divided it among them. Umar presented it to us but we found it less than our right. We, therefore returned it to him and refused to accept it.
Grade: Sahih

Hadith #3036 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Anas ibn Malik; Ibn Ishaq محمد بن إسحاق بن يسار‎; Uthman bin Abi Sulaiman عثمان بن أبي سليمان بن جبير بن مطعم; Yahya bin Zakaria bin Abi Zaida يحيى بن زكريا بن أبي زائدة (Sunan Abi Dawud)
Abu Hurairah reported the Apostle of Allaah(ﷺ) as saying “Whatever town you come to and stay in , your portion is in it, but whatever town disobeys Allaah and His Apostle a fifth of it goes to Allaah and His Apostle and what remains is yours.”
Grade: Sahih

Hadith #3039 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Ibrahim bin Mhajr bin Jabir إبراهيم بن مهاجر بن جابر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Ziyad bin Hdyr زياد بن حدير (Sunan Abi Dawud)
A simiar tradition from the Prophet(ﷺ) has also been transmitted by Mu’adh through a different chain of narrators.
Grade: Sahih

Hadith #3136 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Anas ibn Malik; Usamah ibn Zayd; Uthman bin 'Umar bin Fars عثمان بن عمر بن فارس (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) passed Hamzah who was killed and disfigured. He said: If Safiyyah were not grieved, I would have left him until the birds and beasts of prey would have eaten him, and he would have been resurrected from their bellies. The garments were scanty and the slain were in great number. So one, two and three persons were shrouded in one garment. The narrator Qutaybah added: They were then buried in one grave. The Messenger of Allah (ﷺ) asked: Which of the two learnt the Qur
Grade: Hasan

Hadith #3574 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abu Hurairah; Malazm bin 'Amr - Lazaym ملازم بن عمرو اليمامي - لزيم; Musa bin Njd'h al-Hnfy موسى بن نجدة الحنفي اليمامي; Umar bin Yonus bin al-Qasim عمر بن يونس بن القاسم (Sunan Abi Dawud)
‘If a judge passes a judgment having exerted himself to arrive at what is correct, and he is indeed correct, he will have two rewards. If he passes judgment having exerted himself to arrive at what is correct, but it is incorrect, he will have one reward.'” I narrated it to Abu Bakr bin Hazm and he said: “This is what Abu Salamah narrated to me from Abu Hurairah.
Grade: Sahih

Hadith #3826 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Khalid bin Mysrh al-Tfawy خالد بن ميسرة الطفاوي; Mua'wiya bin Qurrah bin Iyas معاوية بن قرة بن إياس بن هلال; Qurrah bin Iyas (Sunan Abi Dawud)
I ate garlic and came to the place where the Prophet (ﷺ) was praying; one rak’ah of prayer had been performed when I joined. When I entered the mosque, the Prophet (ﷺ) noticed the odour of garlic. When the Messenger of Allah (ﷺ) finished his prayer, he said: He who eats from this plant should not come near us until its odour has gone away. When I finished the prayer, I came to the Messenger of Allah (ﷺ) and said: Messenger of Allah, do give me your hand. Then I put his hand in the slee
Grade: Sahih

Hadith #3888 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Abbas ibn 'Abd al-Muttalib; Amir al-Sha'bi عامر الشعبي; Anas ibn Malik; Sharayk bin 'Abdullah bin Abi Namr شريك بن عبد الله بن أبي نمر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yazid bin Harun يزيد بن هارون (Sunan Abi Dawud)
I passed by a river. I entered it and took a bath in it. When I came out, I had fever. The Messenger of Allah (ﷺ) was informed about it. He said: Ask AbuThabit to seek refuge in Allah from that I asked: O my Lord, will the spell be useful? He replied: No, the spell is to be used except for the evil eye or a snake bite or a scorpion sting. Abu Dawud said: Humah means the biting of snakes and sting of the poisonous insects.
Grade: Hasan

Hadith #3922 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur-Razzaq عبد الرزاق بن همام; Frwh bin Msyk; Ma'mar bin Rashid معمر بن راشد; Mkhld bin Khalid bin Yazid مخلد بن خالد بن يزيد الشعيري (Sunan Abi Dawud)
“An omen is in a dwelling, a woman or a horse.” Abu Dawud said: This tradition was read out to al-Harith b. Miskin and I was witness. It was said to him that Ibn Qasim told him that Malik was asked about evil omen in a horse and in a house. He replied: There are many houses in which people lived and perished and again others lived therein and they also perished. This is its explanation so far as we know. Allah knows best. Abu Dawud said: ‘Umar (ra) said: A mat in a house better than a woma
Grade: Sahih

Hadith #4292 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur Rahman bin Thabit عبد الرحمن بن ثابت بن ثوبان العنسي; Hashim bin al-Qasim bin Muslim هاشم بن القاسم أبو النضر - قيصر; Jubayr bin Nufayr al-Hadrami; Makhul al-Shami/al-Damashiqi مكحول الشامي; Malik bin Yakhamar مالك بن يخامر; Mu'adh ibn Jabal (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: you will make a secure peace with the Byzantines, then you and they will fight an enemy behind you, and you will be victorious, take booty, and be safe. You will then return and alight in a meadow with mounds and one of the Christians will raise the cross and say: The cross has conquered. One of the Muslims will become angry and smash it, and the Byzantines will act treacherously and prepare for the battle.
Grade: Sahih

Hadith #4372 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur-Razzaq عبد الرزاق بن همام; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
The verse “The punishment of those who wage war against Allah and His Apostle, and strive with might and main for mischief through the land is execution, or crucifixion, or the cutting off of hands and feet from opposite side or exile from the land…most merciful” was revealed about polytheists. If any of them repents before they are arrested, it does not prevent from inflicting on him the prescribed punishment which he deserves.
Grade: Hasan

Hadith #4395 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdur-Razzaq عبد الرزاق بن همام; Aisha bint Abi Bakr; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; Ma'mar bin Rashid معمر بن راشد; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان; Urwa ibn al-Zubayr عروة بن الزبير (Sunan Abi Dawud)
A Makhzuml woman used to borrow goods and deny having received them, so the prophet (ﷺ) gave orders and her hand was cut off. Abu Dawud said: Juwairiyyah has transmitted it from Nafi from Ibn ‘Umar or from Safiyyah daughter of Abu ‘Ubaid. This version adds: The prophet (ﷺ) got up and gave an address saying : Is there any woman who repents to Allah, the Exalted, and to his Apostle? He said it three times, That( woman) was present there but she did not get up and speak. Ibn Ghunj transmitt
Grade: Sahih

Hadith #4557 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul Samad bin 'Abdul Warith bin Sa'id عبد الصمد بن عبد الوارث بن سعيد; ibn Abbas; Ikrama عكرمة; Qatada قتادة; Shu'bah bin al-Hajjaj شعبة بن الحجاج (Sunan Abi Dawud)
The Prophet (ﷺ) said: The fingers are equal. I asked: Ten camels for each? He replied: Yes. Abu Dawud said: Muhammad b. Ja’far transmitted it from Shu’bah, from Ghalib, saying: I heard Masruq b. Aws ; and Isma’il transmitted it, saying: Ghalib al-Tammar transmitted it to me through the chain of Abu al-Walid ; and Hanzlah b. Abi Safiyyah transmitted it from Ghalib through the chain of Isma’il.
Grade: Sahih

Hadith #4576 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdullah bin Burayda bin al-Husayb عبد الله بن بريدة بن الحصيب الأسلمي; Burayda bin al-Husayb; Ubaidullah bin Musa bin Abi al-Mukhtar عبيد الله بن موسى بن أبي المختار باذام; Yusuf bin S'hyb al-Kndy يوسف بن صهيب الكندي الكوفي (Sunan Abi Dawud)
Two women of Hudhail fought together and one of them threw a stone at the other and killed her. They brought their dispute to the Messenger of Allah (ﷺ) who gave judgement that a male or female slave of the best quality should be given as compensation for her unborn child, and he fixed it to be paid by the woman’s relatives on the father’s side. He made her sons and those who were with them her heirs. Hamal b. Malik b. al-Nabighah al-Hudhali said: Messenger of Allah ! how should I be fined
Grade: Sahih

Hadith #4791 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; Mujahid bin Jabir مجاهد بن جبر; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Sulaiman al-A'mash الأعمش / سليمان بن مهران (Sunan Abi Dawud)
A man asked permission to see the Prophet (ﷺ), and he said: He is a bad son of the tribe, or: He is a bad member of the tribe. He then said : Give him permission. Then when he entered, he spoke to him leniently. `A’isha asked : Apostle of Allah! You spoke to him leniently while you said about him what you said! He replied: The one who will have the worst position in Allah’s estimation on the Day of Resurrection will be the one whom people left alone for fear of his ribaldry.
Grade: Sahih

Hadith #5050 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abu Ishaq al-Sabay'ai' أبو إسحاق السبيعي عمرو بن عبد الله; Ammar bin Razayq عمار بن رزيق; Amr bin Sharhbayl, Abu Maysara عمرو بن شرحبيل الهمداني أبو ميسرة الكوفي (Sunan Abi Dawud)
when any of you goes to his bed, he should dust his bedding with the inner extremity of his lower garment, for he does not know what has come on it since he left it. He should then lie down on his right side and say: In Thy name, my mercy on it, but if Thou lettest it go, guard it with that which Thou guardest Thy upright servants.
Grade: Sahih

Hadith #5062 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abdul 'Aziz bin Muhammad al-Daruradi عبد العزيز بن محمد الدراوردي; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Muhammad bin Ka'b bin Sulaym al-Qarzi محمد بن كعب بن سليم بن أسد القرظي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
Fatimah complained to the Prophet (May peace be upon him) of the effect of the grinding stone on her hand. Then some slaves (prisoners of war) were brought to him. So she went to him to ask for (one of) them, but she did not find him. She mentioned the matter to ‘A’ishah. When the prophet (May peace be upon him) came, she informed him. He (the prophet) visited us (Ali) when we had gone to bed, and when we were about to get up, he said: stay where you are. He then came and sat down between us
Grade: Sahih

Hadith #5088 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; Abd al-Jlyl bin Atyh عبد الجليل بن عطية القيسي أبو صالح; Abdur Rahman bin Abi Bakra عبد الرحمن بن أبي بكرة; Abu 'Amir al-'Aqdi عبد الملك بن عمرو القيسي أبو عامر العقدي; Ja'far bin Maymun al-Tamimi جعفر بن ميمون التميمي بياع الأنماط; Muhammad bin al-Muthna - al-Zaman محمد بن المثنى أبو موسى - الزمن (Sunan Abi Dawud)
Aban ibn Uthman said: I heard Uthman ibn Affan (his father) say: I heard the Messenger of Allah (ﷺ) say: If anyone says three times: “In the name of Allah, when Whose name is mentioned nothing on Earth or in Heaven can cause harm, and He is the Hearer, the Knower” he will not suffer sudden affliction till the morning, and if anyone says this in the morning, he will not suffer sudden affliction till the evening. Aban was afflicted by some paralysis and when a man who heard the tradition beg
Grade: Sahih

Hadith #5108 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-Nadr bin Muhammad النضر بن محمد; Ikrama bin 'Ammar عكرمة بن عمار العجلي أبو عمار اليمامي (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone asks (you) for refuge for the sake of Allah, give him refuge; and if anyone asks you (for something) for the pleasure of Allah, give him. Ubaydullah said: If anyone asks you for the sake of Allah.
Grade: Hasan Sahih

Hadith #5199 - Sunan Abi Dawud - Abbas bin 'Abdul 'Azeem al-'Anbari عباس بن عبد العظيم العنبري; al-'Aswad bin 'Amir Shadhan الأسود بن عامر شاذان; ibn Abbas; Sa'id bin Jubayr سعيد بن جبير الأسدي; Salmah bin Kahayl al-Hadrami سلمة بن كهيل بن حصين; Umar ibn al-Khattab (Sunan Abi Dawud)
one who is riding should salute one who is walking. He then mentioned the rest of the tradition.
Grade: Sahih